Persepsi Pemustaka terhadap Kesesuaian Koleksi Perpustakaan di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Ramadhani, Nia; Rahmah, Elva; Marlini, Marlini (Lembaga Yasin AlSys, 2026)
Collection suitability is a key aspect of service quality because it is directly related to a library’s ability to meet users’ information needs, yet in-depth qualitative studies exploring users’ perceptions of collection suitability in provincial public libraries remain limited. This study aimed to understand library users’ perceptions of collection suitability at the Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat (West Sumatra Provincial Archives and Library Office) in terms of relevance, adequacy, and accessibility of the collection. A qualitative descriptive approach was employed through in-depth interviews, observation, and documentation involving users selected purposively based on the intensity and breadth of their experience in utilising the library’s collections. Data were analysed through the stages of data reduction, data display, and conclusion drawing, with validity tested using source and technique triangulation. The findings show that, in general, users perceive the library’s collection as reasonably suitable for their information needs, particularly for reading, studying, and educational support, with novels, textbooks, and reference books as the most frequently used types of materials. However, users also highlight limitations in the currency of the collection, the depth of certain subject areas, and access to digital collections. The study concludes that the suitability of the library’s collection is at a moderately good level but still requires continuous development, with implications for the need for regular collection updates, expansion of subject coverage, and strengthening of digital collections to enhance user satisfaction and the effectiveness of public library services.